1999
DOI: 10.1021/jp9922716
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Size and Metal Uptake of Chromium(VI), Molybdenum(VI), and Tungsten(VI) Species on ZrO2-Based Catalyst Precursors

Abstract: Zirconium-supported Me(VI) oxide (Me = Cr, Mo, W) was prepared by the equilibrium adsorption method at pH values 2 and 8 by using as a support either hydrous [ZrO2(383)] or thermally pretreated zirconium oxide [ZrO2(T)]. The prepared solids were characterized by X-ray photoelectron spectroscopy, surface area determinations, electron scanning microscopy and analytical methods. Samples of definite grain size ranges of ZrO2(383) were also compared. The results show that the W-containing samples based on ZrO2(383)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…The W surface densities in the as prepared samples using solutions 1 and 2 as precursors have been determined in the range of 3.4-3.5 and 2.4-2.6 W/nm 2 , respectively. The latter value is higher than that reported in the literature (0.4 W/nm 2 ) for a system obtained by equilibrium adsorption from aqueous nonperoxide solutions at pH 2 using hydrated zirconia as a starting material [14,15].…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…The W surface densities in the as prepared samples using solutions 1 and 2 as precursors have been determined in the range of 3.4-3.5 and 2.4-2.6 W/nm 2 , respectively. The latter value is higher than that reported in the literature (0.4 W/nm 2 ) for a system obtained by equilibrium adsorption from aqueous nonperoxide solutions at pH 2 using hydrated zirconia as a starting material [14,15].…”
Section: Discussioncontrasting
confidence: 62%
“…The Raman spectra of the equilibrated solutions have shown that the adsorbing species in solution 1 [14] concluded that the size of the metatungstate anion is comparable with the main micropore radius of amorphous zirconia. Because the size of the metatungstate ion is larger than that of the peroxo complex, limited adsorption from solution 2 occurs which lowers the uptake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations